2020
DOI: 10.1007/s10956-020-09855-3
|View full text |Cite
|
Sign up to set email alerts
|

Science Teachers’ Attitudes towards Computational Modeling in the Context of an Inquiry-Based Learning Module

Abstract: This study focuses on science teachers' first encounter with computational modeling in professional development workshops. It examines the factors shaping the teachers' self-efficacy and attitudes towards integrating computational modeling within inquirybased learning modules for 9th grade physics. The learning modules introduce phenomena, the analysis of measurement data, and offer a method for coordinating the experimental findings with a theory-based computational model. Teachers' attitudes and selfefficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…While most of our teacher participants scored relatively high on a conceptual pre-assessment of introductory physics (Hestenes et al, 1992), no diagnostic assessment was available at the time to measure teachers' specific abilities with CM. In future studies, we hope to use measures of self-efficacy for CM, which have been used in at least one other study (Langbeheim et al, 2020) as a proxy for computational skills and knowledge that are otherwise challenging to measure in a programming language-agnostic way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While most of our teacher participants scored relatively high on a conceptual pre-assessment of introductory physics (Hestenes et al, 1992), no diagnostic assessment was available at the time to measure teachers' specific abilities with CM. In future studies, we hope to use measures of self-efficacy for CM, which have been used in at least one other study (Langbeheim et al, 2020) as a proxy for computational skills and knowledge that are otherwise challenging to measure in a programming language-agnostic way.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this tendency, multiple U.S. initiatives are calling for science teachers to integrate transdisciplinary content more explicitly, including computing (NRC, 2011;NAE & NRC, 2014). Mueller et al (2008) and Langbeheim et al (2020) are among the few researchers studying science teachers' attitudes about the integration of computing into their disciplines. Mueller et al (2008) identified that K-12 teachers' levels of computer integration in non-computing subjects were dependent upon the teacher's previous "positive outcomes with computers; teacher's comfort with computers; specific beliefs related to the use of computers as an instructional tool; and the teacher's own use of computers at home and at school" (p. 1532).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that fairly short training courses or professional development, in the context of subject matter content that an instructor is quite familiar with, can be very effective training tools. 13 In fact, in our project, two of the three faculty who have taught the course with Python integration had no prior Python programming experience but used a short training course on DataCamp 14 the same one assigned to studentsto learn the basic syntax and structure of Python. We think that the combination of modular programming activities linked to common quantitative learning objectives and a low barrier to entry for instructors will enable broader adoption of computer programming in lower division chemistry courses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, because the programming content is presented in the context of very familiar analytical concepts, like pH and titrations, or calibration curves and linear regressions, instructors were able to quickly pick up the basics of Python for the purposes of this course. There is evidence that fairly short training courses or professional development, in the context of subject matter content that an instructor is quite familiar with, can be very effective training tools . In fact, in our project, two of the three faculty who have taught the course with Python integration had no prior Python programming experience but used a short training course on DataCampthe same one assigned to studentsto learn the basic syntax and structure of Python.…”
Section: Introductionmentioning
confidence: 99%